Serum 25-hydroxyvitamin D level in psoriasis patients: a case-control study - Gupta, Surinder; Garg, Preeti; Gupta, Nakul (International Journal of Research in Dermatology, 2019)
Background: Sufficient level of vitamin D in blood is required for proper regulation of cell differentiation and proliferation. Unchecked proliferation of cells leads to various disease states. Vitamin D also has immunomodulatory effects in the body. Psoriasis is a chronic inflammatory and hyperproliferative disease with vitamin D having an impact on it. This case – control study was done to judge the levels of vitamin D in patients of psoriasis compared to age and sex matched controls. Methods: A case control study was conducted including 50 patients (35 females and 15 males) of chronic plaque psoriasis from dermatology outpatient department of Maharaja Agrasen Medical College (MAMC), Agroha, Haryana, representing patients from north India and 50 healthy controls. Both urban and rural background patients were included. Results: The mean serum 25-hydroxyvitamin D (25-OHD) level in psoriasis patients was 22.865±11.386 ng/ml, whereas in controls it was 35.116±11.048 ng/ml (p<0.001). Serum level of 25-OHD in psoriatic patients was deficient (<20 ng/ml) in 26 (52%), insufficient (20-30 ng/ml) in 8 (16%) psoriatic patients. Conclusions: High prevalence of low vitamin D level was found in this study. We infer that vitamin D does play a role in the pathogenesis, precipitation, exacerbation, or treatment resistance of psoriasis.